STRATEGI MENJAGA SALAT DALAM KEHIDUPAN MUSLIM PERSPEKTIF AL-QUR’AN: STUDI TAFSIR TEMATIK - Adlan Maghfur; Lailatul Mu'jizati; Ayu Annisa; Ahmad Yasin (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This study is motivated by the phenomenon that many Muslims still neglect prayer (salat), both in terms of punctuality, concentration, and consistency in its performance. This condition indicates that prayer, as a primary obligation in Islam, has not been properly maintained in daily life. Therefore, this study aims to examine the concept of maintaining prayer according to the Qur’an and the strategies that can be applied to preserve and perform prayer consistently (istiqamah). This research employs a library research method using a thematic interpretation (maudhu’i) approach. Primary data sources were obtained from Qur’anic verses related to maintaining prayer, while secondary data were collected from Qur’anic commentaries (tafsir), hadiths, scientific journals, dictionaries, and other relevant literature. Data collection techniques were conducted through documentation methods by systematically reviewing various relevant sources. The findings reveal that the concept of maintaining prayer in the Qur’an is not limited to the outward performance of prayer, but also includes preserving its pillars, validity requirements, etiquette, recommended practices (sunnah), and solemnity (khushu’) in prayer. In addition, this study identifies several strategies for maintaining prayer according to the Qur’an, including the application of targhib and tarhib methods as forms of motivation and warning, choosing a positive social environment by associating with people who maintain prayer, habituating congregational prayer, and observing prayer times with discipline. These strategies are expected to serve as spiritual guidance efforts in improving the quality of worship and the religious awareness of Muslims.